Effects of ascorbic acid applied by two hydrocooling methods on physical, chemical and sensory attributes of green leaf lettuce stored at 5 °C - Esparza Rivera, Juan Ramon, author; Stone, Martha B., advisor; Kendall, Patricia, advisor; Pilon-Smits, Elizabeth, committee member; Stushnoff, Cecil, committee member (Colorado State University. Libraries, 2005)
One of the most popular vegetables around the world is lettuce (Lactuca sativa L.). In recent years, the consumption of this vegetable has increased notably, making it one of the most preferred vegetable products in the U.S. However, the quality and shelf life of lettuce are limited by detrimental textural changes (flaccid tissue and reduced turgidity) and browning. Textural changes are caused mostly by dehydration, resulting in a decrease in turgor pressure within cells as well as cellular wall degradation. Browning in lettuce is caused by the production of melanins (dark pigments) from the oxidation of phenolic compounds. These negative changes mainly occur during post harvesting stages (processing and storage). Hence, the implementation of preventive measures to maintain produce quality and nutritional value is necessary. Two treatments used to retard lettuce deterioration include hydrocooling, a procedure used to remove heat from freshly harvested commodities, and the use of antioxidants or reducing agents such as ascorbic acid, which is an alternative to the use of sulfites as a browning inhibitory agent in raw produce. The effects of ascorbic acid applied by two hydrocooling methods on physical, chemical and sensory attributes of fresh cut leaf lettuce during storage at 5 °C were evaluated. Waldmann's dark green lettuce heads were grown in Fort Collins, CO, and harvested manually. Four harvest lots of 55 lettuce heads each were obtained and randomly distributed across 5 treatments, with 11 lettuce heads per treatment. Lettuce heads were treated within 4 hours of harvesting. Treatments included 1) immersion in, or 2) spraying with 1% ascorbic acid solution, 3) immersion in, or 4) spraying with tap water, and 5) control (untreated). Treatment solutions for immersion or spraying were applied at 5 °C for 2 min. After treatment application, lettuce heads were packaged in moisture impermeable polyethylene bags and stored at 5 °C for up to 21 d. Analytical assays included total ascorbate content, Trolox equivalent antioxidant capacity (ABTS+ radical cation assay), total phenolic content (Folin-Ciocalteu method), instrumental color (L*, a* and b* values), texture measurement using TA-XT 2 Texture analyzer, relative water content and a consumer sensory evaluation. All analytical assays were completed at 5 time intervals: before treatment application, and after 1,7, 14 and 21 days of storage at 5 °C. Sensory evaluation panels were conducted on the fourth harvest at 3 storage time intervals: on days 1, 7 and 14 of storage at 5 °C, with a minimum of 30 panelists per session. Lettuce sensory attributes evaluated included appearance, color intensity, flavor, texture, bitterness, tartness and overall acceptability. Sensory attributes were rated using a 15-cm semi-structured scale with 0 = lowest score for the attribute and 15 = highest score for the attribute. Data analyses for all variables were performed using 2-way Analysis of Variance. Differences between means were determined using Least Significant Differences (P < 0.05). Hydrocooling of leaf lettuce by immersion or spraying using 1% ascorbic acid solution increased total ascorbate content for up to 7 days, with an increase of more than 300% in total ascorbate content on day 1 of storage time compared to its initial value before treatments. Still, for all treatments the total ascorbate content of leaf lettuce decreased over time. Hydrocooling by immersion or spraying using cold water or 1% ascorbic acid solution did not prevent post harvest decreases in total ascorbate content in leaf lettuce. Antioxidant capacity of leaf lettuce did not vary among treatments throughout the study. It is possible that the antioxidant capacity of this lettuce variety is based mostly in compounds other than vitamin C, such as phenolics. These results imply that the increase in total ascorbate content in treatments using ascorbic acid solution was not sufficient to affect the antioxidant capacity of leaf lettuce. Hydrocooling with ascorbic acid by immersion increased the total phenolic content of leaf lettuce for up to 7 days, but this could be due to the known interference that ascorbic acid has on the Folin-Ciocalteu assay. Ascorbic acid immersed lettuce was the only treatment that maintained its relative water content throughout the 21 days of storage. Ascorbic acid immersion treatment held the percentage of relative water content in leaf lettuce during the entire experiment, thereby contributing to a firmer texture in leaf lettuce for a longer storage time. Lettuce hydrocooled by spraying with 1% ascorbic acid increased in sensory firmness and became less bitter over the storage time, while hydrocooling by immersion using 1% ascorbic acid negatively affected lettuce appearance and resulted in a darker color over storage time. Water spraying was the treatment for lettuce with the least acceptable appearance and overall acceptability on day 14 of storage time. Further experimentation with the application of ascorbic acid during hydrocooling is needed to fully assess its usefulness in maintaining the quality of leaf lettuce during storage.
Keywords: food science